Comparative Analysis of Commercial and Cooperative Banks in TRNC Banking Sector Using CAMELS Rating System - Görgül, Berk (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Although significant CAMELS performance analysis has been done before in the worldwide literature, a comparative analysis between commercial banks and cooperative banks which is covering the TRNC banking sector has not been made yet. Therefore, this study aims to fulfil this gap in the existing academic literature and lead other upcoming studies would be made at the same scope. In this study, private banks and cooperative banks in the TRNC banking sector will be compared with the help of the CAMELS rating system. The data of 11 commercial banks and 3 cooperative banks were used in the analysis between 2014 and 2019. According to the data obtained in the study, Turkish Bank showed the best performance among the 14 banks covered in the study, while Universal Bank showed the worst performance. Apart from this, the top five banks with the best performance are Turk Bank, Albank, ME-KOOP, Creditwest Bank, and OYAK, respectively. Additionally, it was noteworthy that the performances of Capital Bank and Asbank were also positive. It would be correct to interpret that, these seven banks have improved themselves and performed well compared to previous years. On the other hand, banks with scores below zero are interpreted as having low performance. Banks that perform below zero are Akfinans Bank, Seker Bank, Nova Bank, Near East Bank, Iktisat Bank, DAU-KOOP, and Universal Bank, respectively, from largest to smallest. Although the research sample of cooperative banks is constricted, it is seen that there are two cooperative banks among the top five banks with the best performance, considering the six years discussed.

ÖZ: Dünya literatüründe çok sayıda CAMELS performans analizi çalışmaları yapılmış olmasına karşın bu çalışmaların hiç biri KKTC Bankacılık Sektörü içerisinde yer alan ticari ve kooperatif bankaların karşılaştırılmasında kullanılmamıştır. Literatürdeki bu eksikliği gidermek adına bu çalışmanın yapılmasına karar verilmiştir. Analizde 2014-2019 yılları arasında aktif faaliyet gösteren 11 adet ticari banka ve 3 adet kooperatif bankasının verileri kullanılmıştır. Çalışmada elde edilen bulgulara göre, araştırmaya dahil edilen bankalar arasından en iyi performansı Türk Bankası gösterirken en kötü performansı da bir başka ticari banka olan Universal Bank göstermiştir. Bunun dışında en iyi performans gösteren ilk beş banka sırasıyla; Türk Bankası, Albank, ME-KOOP, Creditwest Bank ve ÖYAK olarak sıralanmaktadır. Ayrıca Capital Bank ve Asbank’ın ortalama performanslarının da olumlu olması dikkat çekicidir. Bu yedi bankanın önceki yıllara kıyasla kendilerini geliştirdikleri ve performanslarında artış yaşadıklarını söylemek doğru olacaktır. Öte yandan sıfırın altında puan alan bankaların performans düşüklüğü yaşadıklarını söyleyebiliriz. Negatif performans gösteren bankalar iyiden kötüye sırasıyla; Akfinans Bank, Şeker Bank, Nova Bank, Near East Bank, İktisat Bankası, DAÜ KOOP ve Universal Bank’tır. Kooperatif bankalarının araştırma örneklemi sınırlı olmakla birlikte ele alınan altı yıllık periyot dikkate alındığında en iyi performansı gösteren ilk beş banka arasında iki adet kooperatif bankasının yer alması son derece dikkat çekici bir bulgu olmuştur.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2022. Supervisor: Prof. Dr. Eralp Bektasş.
Keywords: Thesis Tez; Banking and Finance Department; Banks and Banking--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Commercial Banks--Cooperative Banks--Cyprus, North; CAMELS; performance analysis; TRNC; banking